Factors Affecting The Admission Of Applicants To A Medical School - Davis, Campbell John (My University, 1979)
The purpose of this research is to examine the admissions process in which applicants to medical school are selected. It is argued that structural conditions such as a decrease in occupational demand and an increase in educational supply will result in a greater emphasis upon ascriptive values rather than achieved values. A sampling of applicants from 1969 to 1975 who were involved in the admissions process at the medical school was conducted. As well, 73 percent of the 1975 assessors (N=289) who were involved in the admissions process were also analysed. Both 1975 assessors and applicants were mailed a questionnaire which probed their attitudes to those factors which can be present in the selection process. An analysis of the data revealed that academic marks were less differentiated over time and declining in importance in importance in the admissions process. Only sex was found to be increasing in importance over time. Path analysis of the 1975 data demonstrated the direct and indirect effects of ascribed variables such as sex, age, social class, family size and geographical place of residence.
Keywords: Sociology; Sociology